DRAFT REVISED CODE OF PRACTICE ISSUED UNDER SECTION 47S OF THE PROCEEDS OF CRIME ACT 2002 : Search, Seizure and Detention of Property (England and Wales).: Search, Seizure and Detention of Property (England and Wales). (October 2017) - Great Britain., Home Office,
No abstract available